PENGARUH FAKTOR-FAKTOR KEPENDUDUKAN TERHADAP PERTUMBUHAN EKONOMI DI KABUPATENSUMBAWA TAHUN 2011-2020 - Elly Karmeli; A Asmini; N Nurjannah (Pusat Riset dan Publikasi, 2021)
This study aims to know the effect of population growth and labor both partially and simultaneously toward economic growth in Sumbawa District.The type of this study was associative study. The type of data used in this study was quantitative data. The data source was secondary data.The secondary data in this study were population growth, labor and economic growth for the period year of 2010-2020 (time series). The results of study showed that population growth had significant and negative toward economic growth and labor had negative effect toward economic growth in Sumbawa District. It was based on the significant value of labor was 0.025 was lower if compared with significant level of a 0.05 (0.25 < 0.05) so that Ho was accepted and Ha was rejected, if compared with significance value of 10% , the workforce had significant effect toward econommy growth and had positive relationship toward economic growth in Sumbawa District. The value of coefficient determination (R2) was 0.923 or 92.3%, it means that the percentage effect of population growth and labor toward economic growth in Sumbawa District was 92.3% while the remaining of 7.7% was affected by other variable out of this study.